Penentuan Kadar Flavonoid pada Ekstrak Daun Tanaman Menggunakan Metode NIR dan Kemometrik (Determination of Flavonoid in Leave Extracts Using NIR and Chemometric) - Hilmia Lukman; Lestyo Wulandari; Yuni Retnaningtyas (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Flavonoids are a group of natural compounds with variety phenolic structures and are found in plants. The aim of this research was to study whether NIR and chemometric methods could be used to determine the flavonoid content. These methods were compared to UV-Vis spectrofotometry. Flavonoid was extracted from plant leaves by ultrasonic and maceration. NIR spectral data of selected leave extracts were correlated with flavonoid content using chemometric. In this study, the chemometric method that used for quantitative and qualitative analysis were Partial Least Square (PLS) and Linear Discriminant Analysis (LDA), respectively. The PLS R2 calibration was 0.9916499 and RMSEC was 2.1521897. In addition, the R2 of LOOCV and 2-Fold-Cross-Validation were 0.9986664 and 0.9823225, respectively. Furthermore, LDA gave accuracy of 100%. The significance of flavonoid content that have been measured by NIR and UV-Vis spectrofotometry was evaluated with paired samples t-test. In conclusion, flavonoid content that have been measured with both methods gave no significant difference. Keywords: flavonoid, chemometric, LDA, NIR, PLS